European seabass show variable responses in their group swimming features after tag implantation - Georgopoulou, Dimitra G.; Fanouraki, Eleftheria; Voskakis, Dimitris; Mitrizakis, Nikos; Papandroulakis, Nikos (Frontiers in Animal Science, 2022)
The usefulness of acoustic telemetry on the study of movements, interactions, and behaviors has been revealed by many field and laboratory studies. The process of attaching acoustic tags on fish can, however, impact their physiological, behavioral, and growth performance traits. The potential negative eﬀects are still unknown for several species and behavioral attributes. Previous studies have attempted to shed light on the effects of tag implantation on fish, focusing mainly on fish growth and physiological parameters, and one or two behavioral properties mainly on the individual level. However, the effect of this procedure could also be expressed at the group level. This study investigated the short-term effects of dummy and active body-implanted acoustic tags on the group-level swimming performance of adult European seabass (Dicentrarchus labrax) using optical flow analysis. We studied four main swimming performance properties—group speed, alignment (polarization), cohesion, and exploratory behavior. To help in the interpretation of any detected differences, physiological stress-related parameters were also extracted. The results show that the tag implantation procedure has variable effects on the different swimming performance attributes of fish. Group cohesion, polarization, and the group’s exploratory tendency were significantly impacted initially, and the effect persisted but to a lesser extent two weeks after surgery. In contrast, group speed was not affected initially but showed a significant decrease in comparison with the control group two weeks post-surgery. In addition, the physiological parameters tested did not show any significant difference between the control and the treated group 14 days after the onset of the experiment. The findings suggest that the effect of tagging is non-trivial, leading to responses and response times that could affect behavioral studies carried out using acoustic telemetry.